Effectiveness of an improved fall risk assessment form combined with obstacle physical activity testing in preventing falls in older adults hospitalized patients - Wang, Xuan; Li, Wei; Zheng, Meijie; Li, Chengfei; Liang, Ruijing; Yao, Suchan; Liu, Xiaoli; Zhang, Xiaosong; Di, Xiaomin; Lu, Yang (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of personalized preventive interventions guided by an improved Risk Assessment Form and an obstacle physical activity test in preventing falls among older adults hospitalized patients.MethodA single-center, randomized controlled trial was conducted with 320 older adults hospitalized patients (mean age 76.4 ± 6.8 years), who were allocated to either an experimental group (n = 160) or a control group (n = 160). The experimental group received a comprehensive fall risk assessment using an improved form and an obstacle activity test, which subsequently guided personalized prevention measures. The control group was assessed using traditional hospital fall risk screening methods and received standard fall prevention care. The primary outcome was the incidence of falls. Secondary outcomes included injury severity, nursing satisfaction, patient compliance, physical activity improvement, and quality of life. Key areas for process improvement were identified using Failure Mode and Effects Analysis (FMEA).ResultThe experimental group had a significantly lower fall incidence (8.13%) compared to the control group (28.13%). The experimental group also experienced a lower severity of injuries, with a higher proportion of soft tissue injuries and a lower proportion of fractures. Nursing satisfaction, patient compliance rates, physical activity improvement, and quality of life scores were all significantly higher in the experimental group compared to the control group. FMEA identified that failure to implement preventive measures consistently was the highest-risk failure mode in the fall prevention process.ConclusionThe application of personalized fall prevention strategies guided by a comprehensive assessment that combines a multidimensional risk form with a dynamic obstacle physical activity test is effective in reducing falls and injury severity among older adults hospitalized patients. This approach also enhances patient satisfaction, compliance, and quality of life, and is recommended for broader implementation in inpatient settings.